The Effect of Motivation on Students’s Mathematics Learning Outcomes in the New Normal Era - Habibullah Habibullah; Yolpin Durahim; Tubagus Pamungkas; Maria Lidwina Ika Haryundari; Rusnila Rusnila (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
Motivation has a very important role in encouraging students to study with full attention and concentration in receiving lessons so that the expected learning objectives can be achieved, one of which is indicated by increased learning outcomes. This research aimed to know the effect of motivation on students' mathematics learning outcomes. This type of research is a correlational study using a survey method. The event surveyed in this study is the effect of motivation on students' mathematics learning outcomes in the new normal era. The subjects of this study were 115 students from one of the state junior high schools in Batam City who were selected using a random sampling technique. Data collection techniques in this research used a questionnaire. The data collected is data about students' motivation and mathematics learning outcomes which were analyzed using descriptive and inferential statistics. The results showed that the average value of student learning outcomes was in the medium category, which was 65.48. While the value of the percentage of students' learning motivation on each criterion shows that students have a high enough learning motivation during the mathematics learning process. Meanwhile, based on the results of the correlation test, shows a positive relationship with the correlation value, which is in the low category.